Apakah Sosial Media Influencer Sebagai Mediasi dapat Mempengaruhi Product Quality dan Brand Image Terhadap Purchasing Decision Konsumen Produk Suplemen Kesehatan yang ada di Pasar ? - Mohamad Zein Saleh (Green Publisher Indonesia, 2025)
Consumers have the choice to purchase or not buy products on the market. Because of this freedom, consumers are often influenced by certain situations and conditions, such as quality and brand image. The market is a place to prove that products produced by producers are affordable to consumers. With the growth of social media, the role of influencers has become important as parties who influence consumers to buy the products they produce. This study shows that product quality has a positive and significant influence on social media influencers. Brand image does not significantly influence social media influencers. Social media influencers play a significant role in shaping consumer purchasing decisions. The better the brand image, the greater its influence on purchasing decisions through social media influencers. The higher the product quality, the greater its influence on purchasing decisions through social media influencers.